Socioscientific Issues in Science Education: An opportunity to Incorporate Education about Risk and Risk Analysis?. Issue 12 (7th May 2021) - Schenk, Linda; Hamza, Karim; Arvanitis, Leena; Lundegård, Iann; Wojcik, Andrzej; Haglund, Karin
Abstract: Socioscientific issues (SSI) concern social issues, often lacking simple solutions, that relate to science and often also risk controversies. SSIs have become an established part of science education, aiming to teach students not only about content knowledge but also about the nature of science and to offer them practice in argumentation and decision making. We performed a scoping review of the literature on SSI in science education research, in order to investigate if the topics covered would lean themselves to education about risk, and if risk is raised in these works. Using Web of Science we identified 296 empirical publications and 91 theoretical or review publications about SSI teaching in science education. The empirical publications covered studies performed in primary to tertiary school, most commonly upper secondary school (32%). The most frequently taught SSI themes were nature conservation, biotechnology, and climate change. Despite that these, as most of the other identified themes, clearly are connected to risk analysis and risk management, few publications raised the concept of risk and the methods of risk analysis. In fact, almost half (empirical: 48%, theoretical: 49%) did not mention risk at all. We argue that SSIs present an opportunity for risk researchers to engage with educators to incorporate risk in school science education and to contribute in developing teaching materials suitable toward that aim.